An ultrahigh Q-factor dual-band terahertz perfect absorber with a dielectric grating slit waveguide for sensing. (3rd April 2020) - Yan, Fei; Li, Qi; Tian, Hao; Wang, Zewen; Li, Li
Abstract: The terahertz (THz) perfect absorber with ultra-narrow bandwidth at near-unity absorbance has been a challenging issue due to mutual restrictions of elemental requirements in the design. Here, we propose an extremely sharp dual-band THz perfect absorber with an ultrahigh Q -factor and near-unity absorbance by incorporating a Fabry–Perot micro-cavity into a dielectric grating slit waveguide. Full-wave simulation demonstrates that the proposed structure not only achieves ultra-narrow band perfect absorption with an ultrahigh Q -factor of 4600 in the THz regime, but it also shows extraordinary sensing performance with a record figure of merit (FOM) of 2415 at THz frequencies. The optimized guided mode resonance leads to the ultrahigh Q -factor through suppression of the absorption and radiation losses. The enhanced interaction between the cavity localized fields and the analytes significantly improves the THz sensing capability. Our design approach shows a promising future in simple and inexpensive THz biochemical sensors.